Analisis Faktor Determinasi Nilai Perusahaan. - Mugi Rahayu; Herry Subagyo (Universitas Sains dan Teknologi Komputer, 2020)
This research aims to find out and analyze the factors that are predicted to determine the firm value, the factors are liquidity, debt policy, asset turnover, and profitability. The sample used in the mining sector listed on BEI for the period 2014-2018, the sampling technique using purposive sampling, obtained 118 samples. Data analysis uses multiple regressions using the SPSS program version 23. Hypothesis test results found debt policy and asset turnover positively affected firm value, while it did not prove liquidity and profitability affect firm value.